2016
DOI: 10.1117/12.2236221
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the visualization of pure water transport in porous materials by fast, talbot interferometry-based multi-contrast x-ray micro-tomography

Abstract: The spatio-temporal distribution (4D) of water in porous materials plays a fundamental role in many natural and technological processes. The dynamics of water transport is strongly entangled with the material's pore-scale structure. Understanding their correlation requires imaging simultaneously the 4D water distribution and the porous microstructure. To date, 4D images with high temporal and spatial resolution have been mainly acquired by attenuation-based X-ray micro-tomography, whereby pure water is substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…(1)). In previous work, we have demonstrated, for porous building materials, the higher sensitivity of XPCI to pure water content changes in pores with size above the spatial resolution of the tomograms, compared with corresponding results obtained, on the same specimens and with the same X-ray source and detector, by XACI [48,49]. The reason for the higher contrast by XPCI is twofold: 1) the difference in values between pure water and air, normalized by the value of the solid substrate, is larger than the respective normalized difference for the values (see achieves larger values than , for both water and any material phase of the solid substrate, e.g., cement hydration products (see Figure 4(c) in [49]), and at any X-ray photon energy.…”
Section: Introductionmentioning
confidence: 66%
“…(1)). In previous work, we have demonstrated, for porous building materials, the higher sensitivity of XPCI to pure water content changes in pores with size above the spatial resolution of the tomograms, compared with corresponding results obtained, on the same specimens and with the same X-ray source and detector, by XACI [48,49]. The reason for the higher contrast by XPCI is twofold: 1) the difference in values between pure water and air, normalized by the value of the solid substrate, is larger than the respective normalized difference for the values (see achieves larger values than , for both water and any material phase of the solid substrate, e.g., cement hydration products (see Figure 4(c) in [49]), and at any X-ray photon energy.…”
Section: Introductionmentioning
confidence: 66%
“…It has already been shown that DFI can detect sub-resolution features qualitatively 19,26,40,28,[33][34][35][36][37][38][39] , but until now, methods demonstrating quantification of the size of the unresolved porosity have not been presented in published research. In this research, we present a method to estimate the size of the unresolved pores in a material, based tunable grating interferometry performed at the TOMCAT beamline of the Swiss Light Source (Paul Scherrer Institut).…”
Section: Proposed Methodsmentioning
confidence: 99%
“…X-ray absorption-based microCT has successfully been explored for the characterisation of mortar samples for over two decades [Bentz et al, 1994;Chotard et al, 2003;Carrara et al, 2018]. More recently, it has been recognised in the materials science community that X-ray phase-contrast imaging can often deliver images with superior contrast than conventional absorption CT and multi-modal imaging, exploiting the absorption-, phase-contrast and dark-field signals, can provide complementary information as demonstrated with X-ray grating interferometry [Sarapata et al, 2015;Yang et al, 2016bPrade et al, 2016].…”
Section: Speckle Visibility Speckle Size and Angular Sensitivitymentioning
confidence: 99%